The Elimination of Impurities during Coopper Smelting - R. W. Ruddle (The Institute of Materials, Minerals and Mining, 1953)
"Besides copper, iron, silicon, and oxygen, a large number of elements may be present in copper ores, the more important of which are zinc, lead, arsenic, antimony, bismuth, selenium, tellurium, nickel, cobalt and the precious metals; impurities of less importance are calcium, magnesium, aluminium, barium, sodium, potassium, manganese, lithium, fluorine, titanium, uranium, vanadium, tin and molybdenum. All of these elements are eliminated to some degree in the subsequent roasting, smelting and converting operations.Information on the elimination of impurities during the smelting of copper is surprisingly meagre, however, rather more information is available on impurity removal during the smelting of the ore in reverberatory or blast furnaces."